2002
DOI: 10.1074/jbc.m206631200
|View full text |Cite
|
Sign up to set email alerts
|

The hU3-55K Protein Requires 15.5K Binding to the Box B/C Motif as Well as Flanking RNA Elements for Its Association with the U3 Small Nucleolar RNA in Vitro

Abstract: The 15.5K protein directly binds to the 5 stem-loop of the U4 small nuclear RNA, the small nucleolar (sno) RNA box C/D motif, and the U3 snoRNA-specific box B/C motif. The box B/C motif has also been shown to be essential for the association of the U3 small nucleolar ribonucleoprotein-specific protein hU3-55K. We therefore set out to determine how 15.5K and hU3-55K recognize the box B/C motif. By using an in vitro assembly assay, we show that hU3-55K effectively binds a sub-fragment of the U3 snoRNA surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
62
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 42 publications
(112 reference statements)
11
62
0
Order By: Relevance
“…2F), presumably reflecting errors in reverse transcription at the nucleotide that is the site of protein-RNA cross-linking (6, 7). These results are in good agreement with previous predictions of an Rrp9 binding site near the box B/C motif (8,9,11).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…2F), presumably reflecting errors in reverse transcription at the nucleotide that is the site of protein-RNA cross-linking (6, 7). These results are in good agreement with previous predictions of an Rrp9 binding site near the box B/C motif (8,9,11).…”
Section: Resultssupporting
confidence: 83%
“…Two Rrp9 binding sites were mapped in U3, adjacent to the box B/C motif in helices 2 and 4. This location is consistent with previous studies (8,9,11), and the major Rrp9 cross-linking site was confirmed by primer extension. The archaeal dual guide box C/D snoRNP architecture is symmetric with 2 copies each of the orthologues of Nop1, Nop56/58, and Snu13 (15).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Mutagenesis suggests it is the helix-bulge structure, rather than sequence of base-pairing regions, that is crucial for 15.5K binding (Nottrott et al 1999;. Assembly of 15.5K with a radiolabeled fragment of the human U3 snoRNA, containing only the B/C box, was observed directly in HeLa cell nuclear extracts (Granneman et al 2002). Nucleotide analog interference mapping (NAIM) of a box C/D snoRNP reconstituted in Xenopus oocytes suggests that 15.5K interacts only with the box C/D motif in vivo and not with the box CЈ/DЈ (Weinstein Szewczak et al 2002).…”
Section: Introductionmentioning
confidence: 98%